Sosialisasi Komunitas Permainan Tradisional Di Desa Blitar - Deffri Anggara; Feby Elra Perdima; Juwita Juwita; Prakas Ganesa; Jaka Putra (Universitas Dehasen Bengkulu, 2023)
The purpose of this Community Service is to provide information to Blitar Village managers about traditional games such as crank and dragon snake. This activity was carried out directly (face to face) with representatives of the Belitar Seberang village community and the tourism village management committee at the Village Hall with the approval of the local village head. Apart from being packaged in the form of socialization, this activity was also complemented by activities that went directly to the field and practiced traditional games. Based on the results of the activity, it can be concluded that community service activities in Belitar Seberang Village have great benefits for the village in developing their village's potential to make it more famous. Apart from traveling, visitors also get information on traditional games and can play games such as crank and dragon snake. For the Physical Education Study Program itself, apart from being one of the embodiments of the Tridharma of Higher Education in the community, this activity is also a forum for the team of lecturers to channel their knowledge to the community through traditional games.